Infanzia e Covid-19: riflessioni sulla salute mentale e i vissuti dei bambini durante la pandemia - Baldacchini, Alba; Vignola, Francesca (Il sogno della farfalla, 2021)
The aim of this article is to analyze the effects determined by the Covid-19 pandemic on developmental age with specific reference to the children’s life. The authors focus on the clinical, academic and educational context in which children grow after more than one year from the outbreak of the pandemic. Following an overview of the international and national scientific literature, the paper describes the consequences that this long period has had on mental health and adaptability, and reports a series of thoughts, emotions and experiences shared directly by children. The paper then focuses on the psychotherapeutic work, highlighting both positive and critical aspects experienced in the online psychotherapy with children carried out in remote modality. Finally, the article, by describing the effects on the affective-relational and educational dimension, analyzes the revolution that schools have faced due to the exceptional circumstances of the pandemic.